Application of Inventory and Sales Management and Application of Digital-Based Payments - Dastin Dastin; Candy Candy (ConCEPt - Conference on Community Engagement Project, 2023)
This scientific paper is conducted to analyze the problem that micro, small, and medium enterprise Lucky Photo Studio faced in his business operation along with the alternative solution that can be applied to resolve the problem, which there’s some problems that occurs in Lucky Photo Studio such as insufficient inventory records, unorganized bookkeeping, and cash based payment that are very conventional, according to the statement above there are multiple solutions that given to the enterprise, for example, system that designed for inventory and bookkeeping to assist the business activities, also there is a QR code which is a non cash based payment that the customers can choose to use that has been applied in the enterprise.